Hydrological Potential of Jamblang Weir and Evaluation of Cropping Pattern Feasibility in the Jamblang Irrigation Area - Mahmud; Nurdiyanto; Cuandi; Ardiman (International Journal of Social Service and Research, 2025)
This study evaluates the water availability potential of the Jamblang Weir and recommends an optimal cropping pattern for the Jamblang Irrigation Area in Cirebon Regency, West Java. The hydrological analysis used long-term rainfall data and applied the Blaney-Criddle method to estimate crop evapotranspiration, combined with Q80 dependable discharge estimation using the Weibull formula and a comprehensive water balance assessment. Irrigation water requirements were calculated for rice and secondary crops (palawija), considering irrigation efficiency and seasonal planting periods. The dependable discharge (Q80) is a critical metric in irrigation planning, helping to align water availability with crop demand. This study found the dependable flow to be 0.794 m³/s, while peak irrigation demand reached 1.917 m³/s—indicating adequate capacity for intensive cropping. A proposed rice–rice–palawija rotation enables a cropping intensity (CI) of 240%, exceeding national benchmarks and aligning with FAO (2017) efficiency standards for tropical irrigation. By integrating dependable flow, crop water demand, and irrigation efficiency, the study offers a replicable model for adaptive irrigation management. The results highlight the Jamblang Weir’s capacity to support sustainable agriculture even under seasonal climate and discharge variability. This research contributes a technical foundation for developing water-efficient, climate-resilient cropping strategies in weir-dependent irrigation systems.